Conceptualizing internationalization strategies for higher education institutions - Onise Alpenidze (Central and Eastern European Journal of Management and Economics, 2015)
The increased international competition amongst higher education institutions caused by rapid globalization now requires universities to evaluate, alter or devise new and innovative strategies which will enable them to boost their international activities. There is a need to gain a competitive advantage in attracting more local and international students, involving staff in international exchange programs, conducting joint research, establishing collaborative degree and exchange programs, etc. This ongoing study aims to propose a synthesized conceptual framework of higher education internationalization which links strategic management concepts with higher education, thus consolidating various components by taking into account influential factors such as the dynamics of the external academic environment and organizational resources. The framework outlined in this paper provides a good basis for further empirical research as well as a practical planning scheme for higher education managers.
Keywords: M10; L21; I23; 330; Globalization; Higher Education; Strategic Management; Internationalization; Globalization; Higher education management